1977
DOI: 10.1246/bcsj.50.222
|View full text |Cite
|
Sign up to set email alerts
|

Formose Reactions. II. The Photochemical Formose Reaction

Abstract: Under UV irradiation in the presence of an inorganic base, aqueous formaldehyde was found to give pentaerythritol and 2-hydroxymethylglycerol as the main products, accompanied by the concomitant formation of a mixture of sugars and sugar alcohols. The results indicate that this photochemical formose reaction is considerably different in product distribution from the thermal formose reaction using the Ca(OH)2 catalyst. The detailed examination of the photochemical formose reaction was carried out in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
1

Year Published

1981
1981
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 14 publications
0
24
1
1
Order By: Relevance
“…This behavior does not support previous suggestions that the formose reaction might have been the basis for a selection process, depending upon differing product compositions produced by various minerals (Cairns-Smith et al, 1972). Shigemasa (1977) reported that irradiation of 8 M formaldehyde containing 0.62 M Na2CO 3 produced 2-hydroxymethylglycerol and pentaerythritol as major products. A more recent report (Irie 1989) also describes a highly selective synthesis of ethylene glycol and pentaerythritol via ~-irradiation of dehyde in the presence of 0.05 M K2CO 3 for 10 h and analyzed by GC and HPLC after carrying out a reduction with sodium borohydride.…”
Section: Resultscontrasting
confidence: 93%
“…This behavior does not support previous suggestions that the formose reaction might have been the basis for a selection process, depending upon differing product compositions produced by various minerals (Cairns-Smith et al, 1972). Shigemasa (1977) reported that irradiation of 8 M formaldehyde containing 0.62 M Na2CO 3 produced 2-hydroxymethylglycerol and pentaerythritol as major products. A more recent report (Irie 1989) also describes a highly selective synthesis of ethylene glycol and pentaerythritol via ~-irradiation of dehyde in the presence of 0.05 M K2CO 3 for 10 h and analyzed by GC and HPLC after carrying out a reduction with sodium borohydride.…”
Section: Resultscontrasting
confidence: 93%
“…2) (Schwartz and de Graaf 1993a). Other nonsugar products have been observed from photochemical formose reactions by others (Shigemasa et al 1977). …”
Section: Photocatalysis and Reaction With Ch 3 Chomentioning
confidence: 76%
“…For example, HCHO photochemically reacts to give mostly pentaerythritol (Schwartz and De Graaf 1993), among other nonsugar products ( Fig. 2) (Shigemasa et al 1977). …”
Section: Prebiotic Sinks For Hchomentioning
confidence: 99%
“…Über die photochemische Umwandlung des Formaldehyds (FA) in Zucker und Zuckeralkohole in wäßrigen Lösungen haben erstmals Moore und Webster [1], später Baly, Heilbron und Barker [2,3] und neuerdings Shigemasa, Matsuda, Sakazawa und Matsuura [4] berichtet. Im Hinblick auf das von Hoyle und Wickramasinghe [5] diskutierte -aber keineswegs überzeugend bewiesene -Vorkommen von Zuckern und Cellulose im interstellaren Raum ist interessant, daß Zucker und zuckerähnliche Stoffe auch durch Einwirkung von y-Strahlen auf FA entstehen, der in Silikatgerüsten, wie sie in Zeolithen vorliegen, absorbiert ist [6].…”
Section: Einleitung Und Problemstellungunclassified